Effect of Planting Time on Growth and Corm Yield of Chinese Water Chestnut (Eleocharis dulcis) in the Mekong Delta, Vietnam - Quoc, Dao Phu; Nga, Nguyen Phi; Thach, Le Buu (Asian Journal of Agriculture and Rural Development, 2021)
Experiments were conducted to study the effect of time of planting on the performance of Chinese water chestnut in the Mekong Delta in Vietnam over a single investigation. Plants of a local clone were planted in early January, March, May, July, September, or November and grown for four months. During the experiments, the photoperiod ranged from 11.2 to 12.6 h. The average daily mean temperature across the different cropping periods ranged from 27.70C to 29.10C. Information was collected on chlorophyll fluorescence, plant growth, and yield. Chlorophyll fluorescence (Fv/Fm) was greater than 0.7 in all the treatments (non-stressed), except for the first time of planting and at the end of growing. Corm yield was higher with a planting in May (525 g/plant), November (440 g/plant), and March (325 g/plant), intermediate with a planting in July (196 g/plant), and lower with a planting in January (116 g/plant) and September (55 g/plant). There were strong correlations between yield and the number of stems/plant (r = 0.84), and between yield and stem weight (r = 0.84). These results indicate that acceptable commercial yields can be achieved with water chestnut planted in May in this area.